METAPHOR OF MODALITY IN CLASSROOM INTERACTION - Raissa Sati; Siti Aisah Ginting; Indra Hartoyo (Universitas Negeri Medan, 2021)
METAPHOR OF MODALITY IN CLASSROOM INTERACTION *Raissa Sati ** Dr. Siti Aisah Ginting, M.Pd **Indra Hartoyo, S.Pd, M. Hum ABSTRACT This study aims at analyzing the types and realization of metaphor of modality in classroom interaction of grade eleven Global Prima National Plus Medan. Qualitative research design was used by the researcher to conduct this study. The subjects of this study were the teacher and the students in grade eleven Global Prima National Plus Medan in academic 2018/2019. The data were collected by observed and recorded to find the types of metaphor of modality being used and also to find out how the metaphor of modality is realized in classroom interaction. The data were analyzed by using Miles and Huberman data analysis technique. The findings of the study show that teacher and students used all the types of metaphor of modality in classroom interaction, such as modalization (probability 86,79% with 46 occurances, usuality 1,88% with 1 occurance) and modulation (obligation 3,77% with 2 occurances, inclination 7,54% with 4 occurances) . Metaphor of modality in classroom interaction was realized by the category probability (think, believe, possible), usuality (ussually), obligation (be obligied to) dan inclination (be allowed, recommend, permission). Key words: Teaching, English, Culinary.